Integrasi Pembelajaran Budaya Sapaan Jepang melalui Bahasa untuk Meningkatkan Pemahaman Siswa SMA terhadap Keberagaman Budaya - Sakariah, Dewi Saraswati; Widiandari, Arsi (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This community service activity aims to increase high school students' understanding of cultural diversity through Japanese language learning, especially aisatsu (greeting) material. The activity was carried out at SMA Negeri 1 Semarang as part of the